Phosphoserine-loaded chitosan membranes promote bone regeneration by activating endogenous stem cells - Ke, Yue; Ye, Yu; Wu, Jintao; Ma, Yanxia; Fang, Yuxin; Jiang, Fei; Yu, Jinhua (Frontiers in Bioengineering and Biotechnology, 2023)
Bone defects that result from trauma, infection, surgery, or congenital malformation can severely affect the quality of life. To address this clinical problem, a phosphoserine-loaded chitosan membrane that consists of chitosan membranes serving as the scaffold support to accommodate endogenous stem cells and phosphoserine is synthesized. The introduction of phosphoserine greatly improves the osteogenic effect of the chitosan membranes via mutual crosslinking using a crosslinker (EDC, 1-ethyl-3-(3-dimethyl aminopropyl)-carbodiimide). The morphology of PS-CS membranes was shown by scanning electron microscopy (SEM) to have an interconnected porous structure. The incorporation of phosphoserine into chitosan membranes was confirmed by energy dispersive spectrum (EDS), Fourier Transforms Infrared (FTIR), and X-ray diffraction (XRD) spectrum. The CCK8 assay and Live/Dead staining, Hemolysis analysis, and cell adhesion assay demonstrated that PS-CS membranes had good biocompatibility. The osteogenesis-related gene expression of BMSCs was higher in PS-CS membranes than in CS membranes, which was verified by alkaline phosphatase (ALP) activity, immunofluorescence staining, and real-time quantitative PCR (RT-qPCR). Furthermore, micro-CT and histological analysis of rat cranial bone defect demonstrated that PS-CS membranes dramatically stimulated bone regeneration in vivo. Moreover, H&E staining of the main organs (heart, liver, spleen, lung, or kidney) showed no obvious histological abnormalities, revealing that PS-CS membranes were no additional systemic toxicity in vivo. Collectively, PS-CS membranes may be a promising candidate for bone tissue engineering.